Hyaluronic acid in gynecology and obstetrics - Anna Małgorzata Łopuszyńska; Łukasz Ochyra; Mateusz Pawlicki; Halina Piecewicz-Szczęsna (Kazimierz Wielki University, 2022)
Introduction: Hyaluronic acid (HA) is a polysaccharide classified in the group of glycosaminoglycans. Naturally it occurs in the dermis and is responsible for the elasticity of the skin. In medicine, it can be found cross-linked, partially cross-linked or non-cross-linked, which is associated with different densities and the ability to bind water molecules. It (HA) is used in many areas, including ophthalmology, rheumatology, and dermatology. There are many studies and reports, that it can be used in gynecology and obstetrics in various diseases. Material and methods: The PubMed scientific base was reviewed in 2015-2022 using the keywords hyaluronic acid, gynecology, obstetrics. Results: Intrauterine adhesions are a complication of various procedures performed in the uterine cavity, from curettage to removal of the septum or uterine fibroids. Numerous studies suggest, that hyaluronic acid may be an effective agent in preventing formation of adhesions. For menopausal women, it may relieve symptoms associated with vaginal atrophy. Indocyanine green is used for intraoperative visualization of neoplastic tissues and used in case of cervical cancer. There are reports, that stating hyaluronic acid can increase stability of this substance, which can improve imaging. In the case of hyaluronic acid in the form of vaginal gel, a beneficial effect on hydration and sexual function of women both after childbirth and after menopause was noticed. There are reports of its use in prevention of ovarian failure after chemotherapy and its positive aspects in assisted reproductive techniques. Conclusions: Hyaluronic acid can be used in many gynecological and obstetric diseases, positively influencing the life of women in both fertility and sexual areas and also in the group of cancer patients. Therefore, further large, randomized, multicentre studies confirming action of this substance, determining its dose, method and schedule of administration are important.